Synthetic vs natural scaffolds for human limbal stem cells - Tominac Trcin, Mirna (Croat Med J, 2015)
AIM: To investigate the impact of synthetic electrospun polyurethane (PU) and polycaprolactone (PCL) nanoscaffolds, before and after hydrolytic surface modification, on viability and differentiation of cultured human eye epithelial cells, in comparison with natural scaffolds: fibrin and human amniotic membrane. METHODS: Human placenta was taken at elective cesarean delivery. Fibrin scaffolds were prepared from commercial fibrin glue kits. Nanoscaffolds were fabricated by electrospinning. Limbal cells were isolated from surpluses of human cadaveric cornea and seeded on feeder 3T3 cells. The scaffolds used for viability testing and immunofluorescence analysis were amniotic membrane, fibrin, PU, and PCL nanoscaffolds, with or without prior NaOH treatment. RESULTS: Scanning electron microscope photographs of all tested scaffolds showed good colony spreading of seeded limbal cells. There was a significant difference in viability performance between cells with highest viability cultured on tissue culture plastic and cells cultured on all other scaffolds. On the other hand, electrospun PU, PCL, and electrospun PCL treated with NaOH had more than 80% of limbal cells positive for stem cell marker p63 compared to only 27%of p63 positive cells on fibrin. CONCLUSION: Natural scaffolds, fibrin and amniotic membrane, showed better cell viability than electrospun scaffolds. On the contrary, high percentages of p63 positive cells obtained on these scaffolds still makes them good candidates for efficient delivery systems for therapeutic purposes.